Contribution à l’étude des propriétés structurales, électroniques et élastiques d’un matériau pérovskite magnétique par la méthode FPLAPW. - MAMOUNI, Fatima; AMMOUR, Wafaa (My University, 2024)
Les propriétés structurelles, électroniques et magnétiques des composés perovskites BaXN3(X=K, Rb) vont être calculé par la méthode des ondes planes augmentées (FP-LAPW) qui se base sur la théorie de la fonctionnelle de la densité (DFT) en utilisant le code de Wien2K. Nous avons utilisé l'approximation du gradient généralisé (GGA(06)) pour le terme du potentiel d'échange et de corrélation (XC). Mots Clés : Demi-metal, propriétés magnétiques, GGA-PBE, DFT, ferromagnétique. Abstract: The full-potential linearized augmented plane waves (FP-LAPW) method, which is based entirely on functional density theory (DFT), is used to investigate the structural, electronic, magnetic, and elastic properties of BaXN3(X=K, Rb). This method also employs the Generalized Gradient Approximation (GGA) and a modified Beck Johnson TB-mBJ potential in the exchange correlation term. When the resulting structural properties were examined, the findings showed that our compounds are best stable when they are configured as ferromagnetic materials. The formation energy value demonstrated that these chemicals could be produced experimentally. Additionally, the estimated band structures show that BaXN3(X=K, Rb) exhibits halfmetallic behavior with an indirect band gap. The total and partial density of state curves were used to assess the contributions of the various bands. Additionally, we discovered that the total magnetic moment is an integer of 6 µB, confirming the half-metallic nature. The primary source of the magnetic moment is the spin-polarization of the p electrons in N atoms. The mechanical stability of these compounds has been discovered. The elastic parameters are obtained, including the elastic constants, bulk modulus, anisotropy factor, Poisson's ratio, and Pugh's ratio. Keys Words: Density Functional Theory, Structural Properties, Electronic Properties, Properties and Elastic properties ملخص : تعاظم في اآلونة الحالية االهتمام بالمغناطيس في بعض المواد ب يروف س ك يت والتي لها تطبيقات هامة في مجال أجهزة االلكترونيات الدوارنية . بواسطة طريقة األمواج المستوية خطيا LAPW-FP والتي ترتكز على نظرية الكثافة الدالية DFT مدمجة ضمن برنامج WIEN2K قمنا بحساب الخصائص البنيوية , االلكترونية , المغناطيسية ,المطاطية للمركب ((Rb, K=X(BaXN3 (عن طريق هذه النظرية, قمنا باستعمال تقريب التدرج المعمم GGA-PBE ألجل حساب كمون التبادل – االرتباط )XC )بغية حساب الخصائص البنيوية واإللكترونية المراد معرفتها:وسيط الشبكة ،معامل االنضغاط وعصابات الطاقة .وانتهينا بمقارنة التنبؤات األولية بالنتائج المحققة باألعمال النظرية المتعلقة بها .وقد وجد أن العزم المغناطيسي في هذ المركب يساوي عدد كامل . الكلمات المفتاحية : نصف معدني – الخصائص المغناطيسية - DFT -GGA-PBE -فرو مغناطيسي
Keywords: Demi-metal; propriétés magnétiques; GGA-PBE; DFT; ferromagnétique